Odpowiedzi

2009-12-04T12:43:48+01:00
Zadanie 61

2*(6/27)^(-1):9^1/2= 2*27/6:√9=2*27/6:3=2*27/18=27/9=3

uwaga /-ułamek , ^-do potęgi

zad.62
√5*25^(-1):1/25=√5*1/25:1/25=√5*1/25*25=√5*1=√5
zad.64
³√a*³√b=³√a*b
³√3*³√9=³√3*9=³√27=3
zad.65
√a/√b=√a/b
√8/√2=√8/2=√4=2
zad.66
√3/10*10^1/2-2√3*4 1/2=√3/10*√10-2√3*9/2=
√3-9√3=-8√3
zad.67
√3*√2+(√2)²-2√6=√6+2-2√6=2-√6
zad.68

2√32=2√16*2=2*4√2=8√2
³√24=³√8*3=2³√3

zad.69
√24=√4*6=2√6
³√54=³√27*2=3³√2

zad.70

2√3=√2²*3=√4*3=√12
3³√2=³√27*2=³√54
zad.71

√8*√2*√5*√20=√8*2*5*20=√16*100=√1600=40
zad.72
2/3=2:3=0,66666...=0,(6)-w okresielub =0,67 z nadmiarem
zad.73

5:6=0,833≈0,83 z niedomiarem